Assessment Seakeeping Performance And Operability Model A Fast Craft Using Axe Bow - Romadhoni Romadhoni; Budhi Santoso; IK.A Pria Utama (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2025)
Hull shape affects the characteristics of movement and operability ship itself. Operability ship is at sea the amount of time during which the structure is capable of operating in accordance with the criteria established and high correlation to wave in which criteria will be exceeded. In the research will be carried out analysis of three degrees of freedom of movement and pitch roll heave against the ship model-type crew boat planing hull and AXE Bow size 38 meters on a regular wave with future parameter (heading, speed, mass body, radius gyration, damping and etc.) are presented in the form of graphic images Response Amplitude Operator (RAO). Motion prediction in regular waves has been performed by running a mathematical model developed on the basis of a 3-liner potential theory, and further transformed into the motion in irregular waves through the spectral analysis. The calculation is performed with the help of software computing HydroSTAR Ver.7.1 will be compared with Maxsuft software. This latter analysis was conducted for all level of intensities by referring to the wave scatter data for Natuna Sea, and then correlated to the operational criteria. Results of evaluation exhibits that at full load, operational crew boat could be carried out at significant wave heights Hs ranging from 0.245m up to 3.745m, which has a proportion of occurrence as much as 97.02% to model planing hull and as much as 98.72% to model AXE Bow. Crew boat operation would not be safely conducted at wave heights higher than those, in which their occurrence in Natuna Sea is only 2.720%, model hull planing and is only 0.14% model AXE Bow